2018
DOI: 10.1002/ehf2.12332
|View full text |Cite
|
Sign up to set email alerts
|

Design of the GutHeart—targeting gut microbiota to treat heart failure—trial: a Phase II, randomized clinical trial

Abstract: AimsHeart failure (HF) is a multifactorial disease. Current treatments target only a fraction of the putative pathophysiological pathways. In patients with HF, reduced cardiac output and congestion cause increased gut wall permeability. It has been suggested that leakage of microbial products is detrimental to the heart, at least partly through activation of systemic inflammatory pathways, which again could promote gut leakage. Whether manipulating the gut microbiota can improve cardiac function in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…103 Preliminary results from another ongoing RCT showed that brady yeast can increase LVEF by 5% in patients with systolic HF, and the final results are expected to be achieved in 2020. 104 In conclusion, although studies of probiotics in HF patients remain scarce, this treatment strategy has a great prospect.…”
Section: Gutàtmaoàhf Axis As a Potential Therapeutic Target For Hfmentioning
confidence: 99%
“…103 Preliminary results from another ongoing RCT showed that brady yeast can increase LVEF by 5% in patients with systolic HF, and the final results are expected to be achieved in 2020. 104 In conclusion, although studies of probiotics in HF patients remain scarce, this treatment strategy has a great prospect.…”
Section: Gutàtmaoàhf Axis As a Potential Therapeutic Target For Hfmentioning
confidence: 99%
“…Probiotics have been around for some time now and while they have shown marginal benefit in attenuating myocardial hypertrophy in animal studies, and were associated with left ventricular ejection fraction improvement in one small study, clinical evidence of their benefit in HF is still largely lacking. The ongoing GutHeart study (antibiotic rifaximin vs. the probiotic yeast Saccharomyces boulardii vs. no treatment) will likely shed more light on the role of probiotics and antibiotics in HF . Fecal transplantation on the other hand has had modest success in treating gut dysbiosis, but has significant variability in patient response and carries the potential risk of transmitting harmful infections to the new host .…”
Section: Challenges and Solutions To The Gut Dysbiosis Theorymentioning
confidence: 99%
“…We thank Chun Liang and colleagues for their comments on the design of the GutHeart trial, but disagree with their assertations regarding the potential risk associated with direct modulation of the gut flora. The authors refer to a recent study in which 28 patients with brain fogginess were compared with eight patients without brain fogginess .…”
mentioning
confidence: 98%